1993
DOI: 10.1007/bf01204437
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of embryos into the uterus: How much do technical factors affect pregnancy rates?

Abstract: The parameter studies did not affect the outcome of IVF/ET or FER. Some factors encouraged us to recommend ultrasound-assisted transfer in some cases, and the use of a Frydman catheter for transfer and to encourage the supine position after transfer for longer periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 7 publications
0
49
0
3
Order By: Relevance
“…In three studies, LPS was not employed in the tNC arm [44,46,47]. In only one study, LPS was administered in the tNC arm [48].…”
Section: Tnc Versus Ac With Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In three studies, LPS was not employed in the tNC arm [44,46,47]. In only one study, LPS was administered in the tNC arm [48].…”
Section: Tnc Versus Ac With Suppressionmentioning
confidence: 99%
“…A total of six studies, one RCT [44] and one quasi-randomized [45] and four retrospective cohort studies [46][47][48][49], making a total of 2933 ET cycles, were included.…”
Section: Tnc Versus Ac With Suppressionmentioning
confidence: 99%
“…Moreover, retention of transfer catheter in-situ up to 60 s was recommended in this study. Al-Shawaf et al [7] studied the effects of ultrasound assistance, use of different transfer catheters, and patient position on fertility outcomes and reported that, similar to the former, delayed removal of the catheter was associated with improved outcomes. Conversely, Zech et al [8] stressed that immediate removal of the transfer catheter was associated with better reproductive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Even though immediate removal of the transfer catheter from the uterine cavity may theoretically initiate uterine contractility and, hereby, engender the expulsion of embryos transferred, it has not been clearly demonstrated whether delayed catheter removal contributes to improved fertility outcomes in ART cycles. The results of the studies investigating the timing of transfer catheter removal have remained conflicting [6][7][8][9][10] .…”
mentioning
confidence: 99%
“…Thirty percent of failed implantations can be attributed to poor techniques of embryo transfer. Embryo transfer, therefore, is a vital step in IVF (1)(2)(3). Recently, ultrasound-guided embryo transfer has been reported to improve the clinical pregnancy rate after IVF.…”
Section: Introductionmentioning
confidence: 99%